Effectiveness of the AR-based EASI (exposure analogy social action impact writing) learning model on conceptual understanding of human motion systems in elementary schools - Dyah Lyesmaya; Hillman Arif; Entit Puspita; Ayi Abdurahman; Imam Robandi (Universitas Kanjuruhan Malang, 2026)
Teaching abstract science concepts like the human motion system remains challenging in elementary schools. This study compared four learning models to improve students’ conceptual understanding: AR-integrated EASI, EASI without AR, AR-only, and conventional lecture–discussion. Using a quasi-experimental design, 120 sixth-graders from four Indonesian elementary schools were tested using SOLO Taxonomy-based instruments. Data were analyzed via ANOVA and Tukey HSD tests. Results showed significant differences among groups (p = 0.000). The EASI+AR model yielded the highest improvement (N-Gain = 0.7287) and significantly outperformed AR-only and conventional models. AR alone did not significantly enhance understanding. In conclusion, technology integration requires a solid pedagogical framework like EASI to effectively boost conceptual understanding. Practically, these findings imply that educators and curriculum developers must prioritize pedagogically-driven technology rather than standalone digital tools to optimize elementary science learning.